Classification Of Social Dysfunctions In Patients With Congenital Heart Disease Studying At Higher Education Institutions - AliievaТ. А.; Lesovaya, E. V. (Psychiatry, Neurology and Medical Psychology, 2015)
The state of the emotional sphere, individual psychological characteristics, the level of social adaptation and quality of life, and especially the formation of social dysfunction were investigated in 153 patients with congenital heart disease (CHD) and somatoform vegetative dysfunction of the cardiovascular system (SVD CSS) with the system approach